2022
DOI: 10.1111/bjep.12570
|View full text |Cite
|
Sign up to set email alerts
|

Relating transcription, executive functions and text quality in Grades 2–3: A cross‐lagged panel analysis

Abstract: Background It has been suggested that children's writing is dependent on transcription and executive functions. However, there is a need for more research examining the relationships among those variables in primary school children, given that most existing studies are cross‐sectional and assess transcription and executive functions separately, and there are scarce and mixed longitudinal findings. Aims This study used a cross‐lagged panel model to explore the relationships among transcription skills, executive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…Empirical findings also showed relationships between transcription and EFs. For example, Vieira et al (2023) showed that transcription skills and EFs were related with each other in Grade 2 and 1 year later in Grade 3, but prior performance on these skills did not predict later text quality. Despite emphasizing the importance of cognitive processes, these studies did not consider the role of motivation, specifically, self-efficacy and attitudes, which seem to be the most relevant ones for writing (Camacho et al, 2021).…”
Section: Cognitive Variables In Writingmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical findings also showed relationships between transcription and EFs. For example, Vieira et al (2023) showed that transcription skills and EFs were related with each other in Grade 2 and 1 year later in Grade 3, but prior performance on these skills did not predict later text quality. Despite emphasizing the importance of cognitive processes, these studies did not consider the role of motivation, specifically, self-efficacy and attitudes, which seem to be the most relevant ones for writing (Camacho et al, 2021).…”
Section: Cognitive Variables In Writingmentioning
confidence: 99%
“…Future studies should consider the use of longitudinal designs to follow the trajectory of children's writing-related cognition and motivation throughout schooling and scrutinize their interaction over time (Camacho et al, 2020). Second, due to the lack of sound evidence suggesting the directionally of the link between transcription and executive functions (Vieira et al, 2023), our model specified correlations rather than regressive paths between these variables. Additionally, besides grade, no other variables were controlled in the model, because the inclusion of additional paths could produce unreliable estimates, given our sample size.…”
Section: Predictors Of Writing Performancementioning
confidence: 99%